Analisis Data Nilai Siswa Kelas 8 Berbasis Nilai Pengetahuan Untuk Menentukan Siswa Berprestasi dengan K-Means Clustering (Kasus SMP Negeri 4 Salatiga) - Saputra, Denny Agusto; Pakereng, Magdalena A. Ineke (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
This study aims to analyze data on grade 8 students who excel at SMP Negeri 4 Salatiga using the K-Means Clustering method. The purpose of this analysis is to identify student group patterns based on student academic achievement. The data used in this research are grade 8 students' grades from SMP Negeri 4 Salatiga. The K-Means Clustering method is used to divide students into groups that have comfort in academic achievement. The results showed that there were 35 students who received the highest score when presented, the results obtained were 14.5%, while 35 students who received medium scores when presented, the results obtained were 14.5%, and 172 students who obtained the highest scores if presented, the results obtained were 71%, with the lowest score of a total of 242 students.